Factors facilitating cultural learning in virtual architectural heritage environments: End user perspective - Ibrahim N.; Ali N.M.; Yatim N.F.M. (Association for Computing Machinery, 2023)
Architecture; Design; Architectural heritage; Cultural heritages; Cultural informations; Cultural learning; Design and Development; Information presentation; Presenting informations; Virtual heritage; E-learning